Juggling Between 3R and 1R: The Challenging Life of Teenage Students - Ting, Helen; Ong, Puay Liu; Ong, Puay Tee; Ong, Puay Hoon (Elsevier Ltd., 2010)
This paper will look at how students understand the purposes of education, and how they situate the acquisition of academic literacy (3R) and intercultural competence (1R) in their vision of education and schooling experiences. By looking at the diversity among students, how the students perceive their schooling experiences and their knowledge of the multicultural social reality in Malaysia, this paper attempts to understand and make sense of the everyday living of the students from the point of view of 3R+1R.